2021
DOI: 10.3390/jpm11080692
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Orthodontics: From the Sagittal Position of Lower Incisors to the Facial Profile Esthetics

Abstract: Background: One of the goals of orthodontic treatment is to obtain maximum facial harmony. The sagittal position of the lower incisors plays a significant role in the planning of orthodontic treatment. The aim of the study was to evaluate the relationship between the sagittal position of lower incisors and facial profile esthetics with reference to the skeletal vertical dimension. Methods: There were 200 patients included in the study. Patients were allocated into three groups, depending on the vertical growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…Regarding errors associated with the identification of anthropometric points [10,12,[16][17][18][19][20][21][22], the majority of studies that have evaluated the reproducibility and reliability [1,3,10,12,[20][21][22][23][24][25][26] of individual landmarks have reported errors in point identification. Accurate assessment and repeatability are particularly crucial in growing patients, especially when dealing with the imprecise determination of points A, N, and B.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding errors associated with the identification of anthropometric points [10,12,[16][17][18][19][20][21][22], the majority of studies that have evaluated the reproducibility and reliability [1,3,10,12,[20][21][22][23][24][25][26] of individual landmarks have reported errors in point identification. Accurate assessment and repeatability are particularly crucial in growing patients, especially when dealing with the imprecise determination of points A, N, and B.…”
Section: Discussionmentioning
confidence: 99%
“…The Z and Holdaway angles were chosen for assessing the soft tissue maxillomandibular discrepancy. Both these angles were chosen because they are widely used for soft tissue profile analysis [ 27 ]. A strong correlation was noted between the FSA angle and Z angle in Class I (r-value = 0.836), Class II (r-value = 0.821), and Class III malocclusion subjects (r-value = 0.904; Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…A strong correlation was noted between the FSA angle and Z angle in Class I (r-value = 0.836), Class II (r-value = 0.821), and Class III malocclusion subjects (r-value = 0.904; Table 3 ). A previous study by Derwich et al reported that the Z angle could be used as an accurate diagnostic parameter to assess the convexity of the facial profile [ 27 ]. Contini et al reported that the Z angle could reliably assess facial convexity in different malocclusions with various growth patterns [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…29 The sagittal position of the mandibular incisors is considered to be an essential determinant of facial aesthetics and stability. [30][31][32] Tweed 30 advocated placing the mandibular incisors in an upright position over the basal bone to achieve optimum results.…”
Section: Discussionmentioning
confidence: 99%